Updating on the management of spontaneous intracerebral hemorrhage. - Juan Francisco Piñeiro Martí.; José Ramón Tejera del Valle; Osmany Morales Sabina; Omar López Arbolay. (Medisur)
Spontaneous intracranial haemorrhage is a frequent affection with a devastating effect up the central Nervous system. Although many studies have been carried out worldwide in regards to the treatment of this disease, there is no agreement about the most effective one to treat this terrible disease. Few investigations have been performed with scientific rigour and the inclusion of the sufficient number of patients that allow a best behaviour to be standardised. Our country is also included within this situation and there is no homogeneous attitude for the treatment of this affection but a series of action guides that vary according to the hospital and the group of specialists who have to face them. This article reviews generalities about cerebral haemorrhage and deepens on the most recommended guide lines supported by experience and published articles with the objective of offering, in a coherent way, a group of measures about the surgical management of this disease, deepening on the existing limitations in the present management of the pathology, by means of a review of a wide group of studies published in the world medical literature that has dealt with the topic for years